As Sociedades Contemporâneas e a Gestão Pública do Risco - Santos, Elisabete; Fadul, Élvia (Organizações & Sociedade, 2014)
This paper discusses conceptual and theoretical aspects relating to the constitution of risk in the contemporary society, emphasizing questions concerning environment and services help for collective consumption. Thus, it emphasizes the public dimension of risk management, once in the present context of productive flexibility and globalization; it is no longer possible to dissociate risk from policy. This paper considers particularly the built risk, making explicit the way how that is processed in modernity, and stresses the public dimension of its management. Risk management presupposes, therefore, the constitution of a public sphere to face the challenge of environmental management democratization and of collective services and assets; which demands equalization of the present relationship among state, society and market.